Optimization of surface roughness in drilling using vegetable-based cutting oils developed from sunflower oil - Ozcelik, Babur; Kuram, Emel; Demirbaş, Erhan; Sik, Emrah (Emerald Group Publishing Limited, 2011)
Purpose - The purpose of this paper is to investigate the performance of four cutting oils, two different vegetable-based cutting fluids developed from refined sunflower oil and two commercial types (semi-synthetic and mineral), for surface roughness during drilling of AISI 304 austenitic stainless steel with HSSE tool. Design/methodology/approach - L-9 (3(3)) orthogonal array was used for the experiment plan. Spindle speed, feed rate and drilling depth were considered as machining parameters. Findings - Results were evaluated statistically. Mathematical models based on cutting parameters were obtained from regression analyses to predict surface roughness. ANOVA was used to determine the effect of the cutting parameters on the surface roughness. The performance results were found to be better for vegetable-based cutting oils than that of commercial ones. Originality/value - The paper reports on the use of refined sunflower oil in drilling stainless steel.
Keywords: Steel; Oils; Surface-roughness measurement; Fluids